2019
DOI: 10.1093/mnras/stz2939
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-hydrodynamical models of X-ray photoevaporation in carbon-depleted circumstellar discs

Abstract: The so-called transition discs provide an important tool to probe various mechanisms that might influence the evolution of protoplanetary discs and therefore the formation of planetary systems. One of these mechanisms is photoevaporation due to energetic radiation from the central star, which can in principal explain the occurrence of discs with inner cavities like transition discs. Current models, however, fail to reproduce a subset of the observed transition discs, namely objects with large measured cavities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
(65 reference statements)
3
32
1
Order By: Relevance
“…Recent works from , Ercolano et al (2018), andWölfer et al (2019) suggest that photoevaporation is more effective in disks that are depleted from carbon and oxygen, which results in higher mass-loss rates and a faster dispersal of the outer disk. The outcome of this approach is a lower fraction of relics (up to 45%), which is much lower than standard photoevaporative models, and better suited to explain observations.…”
Section: Comparison With the Observed Transition Disk Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works from , Ercolano et al (2018), andWölfer et al (2019) suggest that photoevaporation is more effective in disks that are depleted from carbon and oxygen, which results in higher mass-loss rates and a faster dispersal of the outer disk. The outcome of this approach is a lower fraction of relics (up to 45%), which is much lower than standard photoevaporative models, and better suited to explain observations.…”
Section: Comparison With the Observed Transition Disk Populationmentioning
confidence: 99%
“…Additional improvements for the model would be to include stars of different masses, considering their respective photoevaporation mass-loss rates (Komaki et al 2021), the evolution of the stellar luminosity during the first million years after formation (Kunitomo et al 2021), and the effect of carbon depletion, which leads to stronger photoevaporation rates (Ercolano et al 2018;Wölfer et al 2019).…”
Section: Comparison With the Observed Transition Disk Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the gas-loss rate due to photoevaporation, we followed Picogna et al (2019) (X-ray and extreme UV). Carbon depletion can have significant effects (Wölfer et al 2019) that we did not take into account. For the profile provided by Picogna et al (2019) we used the scaling with stellar mass from Owen et al (2012).…”
Section: Appendix A: Photoevaporationmentioning
confidence: 99%
“…In the first paper of this series (Picogna et al 2019, hereafter Paper I) we showed the dependence between the stellar X-ray luminosity and the mass-loss rate due to thermal winds generated by the XEUV heating from the central star. Then we studied the influence of carbon depletion (Wölfer et al 2019) and stellar spectra hardness on the mass-loss rates (Ercolano et al 2021, hereafter Paper II). In this following work, we focus on stellar mass dependence and how it might influence disc evolution.…”
Section: Introductionmentioning
confidence: 99%